2022
DOI: 10.3389/ijph.2022.1604228
|View full text |Cite
|
Sign up to set email alerts
|

How Vaccination Rumours Spread Online: Tracing the Dissemination of Information Regarding Adverse Events of COVID-19 Vaccines

Abstract: Objectives: To trace the emergence and dissemination of the most prominent rumours about potential adverse effects of COVID-19 vaccines.Methods: We use a weekly Google Trends search to gather information about what alleged adverse events are being associated with COVID vaccines by the general population. We then use CrowdTangle and Factiva searches to examine how discussions about the five most prominent adverse events have spread through traditional media channels and Facebook.Results: Traditional mass media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Various studies have referred to the negative impact of social media as one of the barriers to the Covid-19 vaccination. Also, a lot of fake news about the Covid-19 origin and treatment, as well as the false vaccination side effects, were spread through these media, which could lead to a change in people's awareness and behavior and their unwillingness to be vaccinated against the virus ( 36 , 37 ). One of the misconceptions in our study was the lack of belief in the necessity of injection for various reasons, which, similar to our results, various studies have shown that the biggest obstacle to vaccination was the lack of belief in its necessity ( 27 , 47 , 49 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have referred to the negative impact of social media as one of the barriers to the Covid-19 vaccination. Also, a lot of fake news about the Covid-19 origin and treatment, as well as the false vaccination side effects, were spread through these media, which could lead to a change in people's awareness and behavior and their unwillingness to be vaccinated against the virus ( 36 , 37 ). One of the misconceptions in our study was the lack of belief in the necessity of injection for various reasons, which, similar to our results, various studies have shown that the biggest obstacle to vaccination was the lack of belief in its necessity ( 27 , 47 , 49 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are lots of reason to reject, delay, hesitancy and refusal of COVID-19 vaccine: Fear of short or long term applications to health, not considering being in a risk group, pregnancy, risk pregnancy, recent abortion, breastfeeding period ( 25 ), misinformation beliefs ( 26 , 27 ), not having enough vaccine-related information ( 26 28 ), concerns over vaccine safety ( 18 , 19 , 26 , 28 , 29 ), structural barriers ( 28 , 30 ), personal experience with the disease ( 31 , 32 ), possible unknown future adverse effects of the vaccine ( 32 , 33 ), social determinants of health ( 23 ), low health literacy ( 23 , 34 ), not trusting the drug companies ( 23 , 27 , 29 ), political ideologies ( 11 , 23 , 35 ), distrust of science and the government ( 19 , 26 , 29 , 33 ). Also, various social media made people hesitate to inject the vaccine by spreading false rumors about the COVID-19 vaccine harms, which could create a major challenge for the health system ( 36 , 37 ). A study in Germany showed that health concerns, Low perceived benefit of vaccination, lack of information, systemic mistrust low perceived risk of contracting COVID-19 and spiritual or religious reasons were reasons for refusing a COVID-19 vaccination ( 16 ).The results of a study showed that believing in the illusion of a vaccine plot, the perceived severity of COVID-19, being a man, household income, not paying attention to conservative parties, and not relying on social media for gaining information about the virus are reasons to willingness to vaccine injection and concerns about vaccine efficacy, individual susceptibility and severity of COVID-19, and the possibility of immunity from previous COVID-19 infection were among the reasons for unwillingness to be vaccinated ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Methods were largely derived from previous investigations using social media data [33,34]. Similar to the previous studies, we used CrowdTangle Search, a service owned by Meta that allows researchers to extract publicly available data on Facebook [35,36]. On January 11, 2022, we extracted all Facebook posts in the BGR Facebook page between the 6-month period of June 1, 2021, through December 31, 2021.…”
Section: Data Collectionmentioning
confidence: 99%
“…First, tracking the evolution of the volume of COVID-related news presents an indicator of public attention [11]. Emerging terms like "infodemic" and rampant misinformation showcase that the relationship between the amount of communication about the pandemic and public attitudes may not necessarily be linear [14,15]. It is, therefore, important to assess how much news coverage is dedicated to COVID-19 as the epidemiological situation evolves.…”
Section: Introductionmentioning
confidence: 99%